Perspektif Hukum Penyelenggaraan Hak Pilih Penyandang Disabilitas Mental Pada Pemilu 2019 - Sembiring, Fachrudin; Siregar, Yemima Hillary (Fakultas Hukum Universitas Andalas, 2024)
Indonesia is a democratic country with one characteristic, that is, sovereignty is in the hands of the people. One of the manifestations of a democratic country is through a general election. Every citizen has the same rights and opportunities in general elections, namely the right to vote. Even so, the granting of voting rights for persons with mental disabilities has only been implemented evenly in the 2019 elections. This is of course guaranteed through Law Number 7 of 2017 concerning General Elections. There are still many things that need to be evaluated from the 2019 Election both in terms of implementation and legal guarantees provided for groups of people with disabilities. The writing of this law uses a normative juridical method in which the approach is based on the main legal material by examining theories, concepts, legal principles related to the right to vote for persons with mental disabilities. Because the KPU has just registered persons with mental disabilities on the final voter list in the 2019 elections, the implementation is still not perfect. There are still many people with mental disabilities who have not been able to exercise their right to vote or vote in the 2019 election. Therefore, it is necessary to carry out an update for the upcoming elections in addition to increasing voter participation as well so that the democratic party can be felt by all Indonesian citizens without exception. It is the responsibility of the state to guarantee the rights of its citizens and create non-discriminatory regulations.